Clinicopathological characteristics and BRCA1/BRCA2 pathogenic variants of patients with breast cancer - Eras, Nazan; Tuncel, Ferah; Altıntas, Zuhal; Erden, Sema (Polish Journal of Pathology, 2024)
Although BRCA genes are well-known breast cancer genes, the clinicopathological features of breast cancer patients carrying BRCA1/2 pathogenic variants have not been adequately defined. The goals of this study were to determine the distribution of BRCA1/2 variants in the Turkish population and its correlation with clinicopathological features. Clinical data of 151 women who underwent BRCA1/2 gene testing at Mersin University Medical Faculty Hospital between 2016 and 2019 were retrospectively analyzed. BRCA1/2 variants were detected as pathogenic (n = 11), variants of uncertain significance (n = 5), likely benign (n = 3), and benign (n = 81) in breast cancer cases. The BRCA1/2 pathogenic variant carriers had a higher histological grade, rate of triple- negative type, Ki-67 proliferation index, and rate of no special type carcinoma than the group without mutation (p = 0.03, 0.01, 0.04, and 0.02 respectively). We analyzed the distribution of variants we detected in women living in our region and found that pathogenic variants in patients with breast cancer were associated with high histological grade, triple-negative type, high Ki-67 proliferation index, and histological type. Studies in diverse populations are needed to establish a clinicopathological relationship with variants more easily.